Storozhenkotettix, a new genus of Trusmaditetrigini (Orthoptera: Tetrigidae) from Mindanao, with notes on Bolivaritettix - Jr., Romeo R. Patano; Skejo, Josip; Amoroso, Victor B.; Kasalo, Niko (Zootaxa, 2024)
The Philippine archipelago houses an incredibly diverse biota, among which are 122 species of pygmy grasshoppers (Orthoptera: Tetrigidae). Many of them belong to genera without proper taxonomic assignment and some genera, e.g., Bolivaritettix are so speciose and ill-defined that working with them is practically impossible. Here, we make a step toward the resolution of these problems by describing a new genus, Storozhenkotettix gen. nov. for Bolivaritettix amphinotoides, resulting in a new combination, S. amphinotoides comb. nov. This species does not seem to be closely related to the type species of Bolivaritettix, but rather to Trusmaditetrix, which is a member of the tribe Trusmaditetrigini. We provide new records of S. amphinotoides comb. nov., together with photographs of living specimens and habitat descriptions. The species was observed along the edges of montane forests and in the disturbed parts within forests. It seems to prefer partially shaded humid habitats.